Catecholaminergic polymorphic ventricular tachycardia: advancing from molecular insights to preclinical models - Schneider, Luca; Begovic, Merima; Zhou, Xiao-Bo; Hamdani, Nazha; Akın, Ibrahim; El-Battrawy, Ibrahim (Journal of the American Heart Association, 2025)
Inherited cardiac channelopathies are linked to a heightened risk of sudden cardiac death. Despite evolving knowledge on different genes for these inherited conditions, for certain subtypes, such as catecholaminergic polymorphic ventricular tachycardia syndrome, the specific genetic causes remain unidentified. The research of the pathophysiological mechanisms underlying catecholaminergic polymorphic ventricular tachycardia syndrome has been conducted through different in vitro and in vivo models, including genetically modified animal models, cardiac‐specific transgenic models, pharmacological interventions in animal models, human‐induced pluripotent stem cell-derived cardiomyocytes in 2‐ and 3‐dimensional cardiac models. Recent research predominantly utilizes human‐induced pluripotent stem cell-derived cardiomyocytes, focusing on genotype-phenotype correlations and pharmacological screening. The integration of cutting‐edge techniques such as clustered regularly interspaced short palindromic repeats/Cas9 genome editing and 3‐dimensional-engineered heart tissues has shed new light on the pathophysiological mechanisms of catecholaminergic polymorphic ventricular tachycardia, potentially enhancing drug therapies as part of personalized medicine approaches. This review emphasizes the diverse insights gained from both in vivo and in vitro studies of catecholaminergic polymorphic ventricular tachycardia, along with the application of these models in various research contexts.